Identification and Determination of Dimensions of Health-Related Quality of Life for Cancer Patients in Routine Care – A Qualitative Study - Schrage, Theresa; Görlach, Mirja; Schulz, Holger; Bleich, Christiane (Frontiers in Psychology, 2022)
Purpose. Continuous patient-reported outcomes (PROs) represent an important addition to current routine care, to identify and address the patient’s needs. The aim of this study was to identify and determine important dimensions of health-related quality of life (HrQoL) in oncological routine care. Methods. In a cross-sectional qualitative study design interviews and focus groups were carried out and recorded. The interviewees were asked for their evaluation on HrQoL in general and in regard to cancer treatment. The material was transcribed and analyzed using qualitative content analysis based on Mayring. The results were presented to and discussed in an expert discussion. Results. Interviews with patients (N=28) and clinicians (N=4) were carried out, as well as five focus groups with clinicians (N=18). Initially, nine deductive and two inductive categories on HrQoL were built. Four categories were excluded following the qualitative content analysis. After the next step, analyzing the expert discussion, one dimension was added and two further categories were excluded. The resulting dimensional system consists of six dimensions: emotional health, physical ailments, autonomy, social functionality, dignity and resources. Conclusions. A dimensional structure of HrQoL in cancer patients in hospital routine care was found, which differs from dimensional structures of existing HrQoL measurements for (cancer) patients. Further research is needed to test and evaluate the presented structure in a large sample of cancer patients to further assess its psychometrical quality criteria.